Estimation of the Proportion of Potential Nondisclosed Men Who Have Sex With Men Among Self-Reported Heterosexual Men With HIV Using a Randomized Response Technique. Issue 5 (13th May 2022) - Chen, Yi; Ruan, Yuhua; Shen, Zhiyong; McNeil, Edward B.; Xing, Hui; Shao, Yiming; Lin, Mei; Lan, Guanghua; Chongsuvivatwong, Virasakdi
Abstract : Applying a randomized response technique, 14.3% of self-reported heterosexual men with HIV in Guangxi, China, were likely to have experienced anal sex within the last 3 years. Abstract : Background: Because of HIV-related stigma and gender minority stigma, the number of men who have sex with men (MSM) among registered HIV/AIDS cases may be underreported in Guangxi, China. In addition to the sensitivity of direct inquiry of sexual identity and behavior, our study aims to determine the proportion of potential nondisclosed MSM (pnMSM) among self-reported heterosexual men with HIV. Method: The study subjects were self-reported heterosexual men with HIV who were diagnosed in recent 20 years in Guangxi, China. A randomized response technique was executed by randomly putting them to secretly answer either whether their birthday was odd or even day, or whether they experienced anal sex in the last 3 years. Personal characteristics were linked with randomized response technique answers for subgroup analysis. Results: The proportion of pnMSM ever having anal sex was estimated to be 14.3% in Guangxi, China. Being younger, having a college or above education level, single, employed, of Han ethnicity, diagnosed with HIV in the past 6 years, and not on antiretroviral therapy were associated with giving positive answer. Conclusions: The reported number of MSM cases with HIV in the past may have been underestimated in Guangxi, China. Information about preexposure and postexposure prophylaxis should be provided to this stigmatized subgroup—pnMSM, especially those who are younger and with a higher socioeconomic status among self-reported heterosexual men with HIV.